International connections in actor training in Australia: tracing Stanislavski's system and Brechtian politics. Issue 2 (3rd July 2019) - Tait, Peta; Beddie, Melanie
ABSTRACT: This article traces the approaches to actor training offered in Australia based on the training backgrounds of influential teachers. The research for this article finds international connections that reveal strong links to approaches originating with Konstantin Stanislavski and Bertolt Brecht. It seeks to understand with whom a teacher studied to explain what was probably learnt and therefore the type of training knowledge that the teacher is likely to pass on to students. The research confirms that international approaches are fundamental to performance training in tertiary conservatorium courses, and the profiles of nine teachers are presented in detail to encapsulate patterns of training and to show the complex nexus of influences and international approaches. The profiles indicate an increasing influence of American approaches in the second half of the twentieth century alongside British ones, but that British influences remain important for European approaches and for political theatre in particular into the twenty-first century. We argue that even where there was a synthesis happening in the teaching of performance in Australia, the influences of major international approaches are identifiable through the training backgrounds of teachers. In this way, it is possible to locate teachers in Australia within actor training internationally.